Aportación al estudio de prácticas mortuorias durante el Período de Desarrollos Regionales. Entierros en vasijas utilitarias del sector central del valle Calchaquí (Salta, Argentina) - Baldini, Lidia; Baffi, Elvira I. (Revista Española de Antropología Americana, 2007)
In this paper we analyze published and unpublished information on sub-adults´ burials in urns from settlements of the Regional Development Period (9th - 15th centuries) in central Calchaquí Valley, Salta, Argentina. We deepen into information about late children´ burials in ordinary vessels, the use of certain words and ideas, and about signs related to mortuary practices.